A dynamically regulated 14-3-3, Slob, and Slowpoke potassium channel complex in Drosophila presynaptic nerve terminals. - Zhou, Y.; Schopperle, W.M.; Murrey, H.; Jaramillo, A.; Dagan, D.; Griffith, L.C.; Levitan, I.B. (Neuron, 1999)
Slob is a novel protein that binds to the carboxy-terminal domain of the Drosophila Slowpoke (dSlo) calcium-dependent potassium (K(Ca)) channel. A yeast two-hybrid screen with Slob as bait identifies the zeta isoform of 14-3-3 as a Slob-binding protein. Coimmunoprecipitation experiments from Drosophila heads and transfected cells confirm that 14-3-3 interacts with dSlo via Slob. All three proteins are colocalized presynaptically at Drosophila neuromuscular junctions. Two serine residues in Slob are required for 14-3-3 binding, and the binding is dynamically regulated in Drosophila by calcium/calmodulin-dependent kinase II (CaMKII) phosphorylation. 14-3-3 coexpression dramatically alters dSlo channel properties when wild-type Slob is present but not when a double serine mutant Slob that is incapable of binding 14-3-3 is present. The results provide evidence for a dSlo/Slob/14-3-3 regulatory protein complex.